Penyuluhan Hukum Tentang Layanan Bantuan Hukum Gratis di Posbakum Rutan Kelas 1 Surakarta - Kurnianingsih, Marisa; Hartanto, Hartanto; Firdaus, Lutfi`ah; Moestofa, Yoesoef (Abdimas Indonesian Journal, 2024)
The principle of "Equality before the law" states that every individual has equal rights before the law and equal treatment in the justice system. This principle emphasizes that all people must be treated fairly and equally in the eyes of the law without discrimination. This principle explains that everyone has equal access to the legal process and justice, without any bias or unfair treatment based on factors such as race, religion, gender or social status. This principle is an important foundation in ensuring justice, protection of human rights, and fair law enforcement for all citizens. The free legal aid program is one way to realize access to law and justice for the poor, which is provided by the state as mandated by the constitution. The provision of legal aid to citizens in Indonesia is an effort to fulfill and at the same time implement a rule of law that recognizes, protects and guarantees the human rights of citizens. Through the provision of free legal aid, it is hoped that people in need can gain access to free legal services that are fair and equitable, and receive appropriate legal protection.